Can We Read Letters? Reflections on Fundamental Issues in Reading and Dyslexia Research - Tønnessen, Finn Egil (Brill, 2015)
The authors use these fundamental analyses and definitions to shed new light on the 'balanced approach to reading instruction', 'reading fluency' and other key concepts. The book also deals with problems in the definition of 'dyslexia' and proposes a method to arrive at clear and fruitful definitions. It concludes with a chapter trying to answer the question of in what sense, or to what extent, it can be claimed that reading and dyslexia research has made progress. Readership: Educational Researchers and their students